Literary stylistics: pedagogical perspectives in an EFL context - Ghazalah, Hasan (1987)
This thesis in concerned with literary stylistics and the interpretation of literary texts in an EFL context. It has the ultimate pedagogical objective of helping non-native students of English to become sensative to stylistic features and functions and later to perform stylistic analysis and stylistic interpretation of texts.